Preparation and Evaluation of A Novel Transdermal Drug Delivery System of Risperidone - Mayank Shukla; Rakesh Singh (Asian Journal of Pharmaceutical Research and Development, 2026)
Psychosis is a severe psychiatric disorder requiring long-term antipsychotic therapy, often limited by poor patient compliance and systemic side effects associated with conventional oral dosage forms. The present study focuses on the formulation and characterization of a transdermal drug delivery system of risperidone to improve therapeutic efficacy, enhance patient compliance, and minimize first-pass metabolism. Transdermal patches were prepared using natural and biocompatible polymers such as xanthan gum and chitosan, which provide excellent film-forming ability, mechanical strength, and controlled drug release properties. The formulation was further optimized by incorporating penetration enhancers including eucalyptus oil and fennel oil to improve the permeation of risperidone across the stratum corneum. The prepared patches were evaluated for physicochemical parameters such as thickness, weight variation, folding endurance, drug content uniformity, moisture content, and in vitro drug release profile. In vitro permeation studies demonstrated that the combination of natural polymers with essential oil-based penetration enhancers significantly improved the sustained release and transdermal flux of risperidone. The study suggests that the developed transdermal patch system could serve as a promising alternative to conventional oral therapy for the effective management of psychosis, offering controlled drug delivery, reduced dosing frequency, and improved patient adherence.